Interviews 2 - Matt, Gerald; Abdul, Lida; Althamer, Pawel; Baladi, Lara; Barney, Matthew; Bourgeois, Louise; Bugaev, Sergei; Capellari, Wolfgang; Cattelan, Maurizio; Djurberg, Nathalie; Dolven, Anne Katrine; Dzama, Marcel; et al. (Wien : Kunsthalle Wien, 2008)
Abdul, Lida ; Althamer, Pawel ; Baladi, Lara ; Barney, Matthew ; Bourgeois, Louise ; Bugaev, Sergei ; Capellari, Wolfgang ; Cattelan, Maurizio ; Djurberg, Nathalie ; Dolven, Anne Katrine ; Dzama, Marcel ; Eitel, Tim ; Furnas, Barnaby ; Haneke, Michael ; Karamustafa, Gülsün ; Kempinas, Zilvinas ; Kenawy, Amal ; Komad, Zenita ; Kozyra, Katarzyna ; Leitner, Paul Albert ; Linder ; Liu Ding ; Lüthi, Urs ; McGinley, Ryan ; Metzel, Olaf ; Neuwirth, Olga ; Noble, Tim ; Ottinger, Ulrike ; Poka-Yio ; Popp, Julius ; Solakov, Nedko ; Solomons, Doron ; Swallow, Ricky ; Tayou, Pascale Marthine ; Tunick, Spencer ; Varga Weisz, Paloma ; Wang Wei ; Ward, Nari ; Webster, Sue ; Wurm, Erwin ; Zaimoglu, Feridun ; Ziervogel, Ralf ; Zmijewski, Artur
boek